Sintesis Keramik Refraktori Al2O3.MnO2.SiO2 Dengan Metoda Sol-Gel dan Sifat Fisikanya Dalam Berbagai Temperatur Kalsinasi - Rahmi Muthia; Deski Beri; Ali Amran (Jurnal Periodic Jurusan Kimia UNP, 2013)
Ceramic oxide Al2O3.MnO2.SiO2 ceramics has relatively high strength, tough electrical capacitance and temperature resistant. It’s synthesized by sol-gel methods using raw materials Tetraethyl Orthosilicates (TEOS), Al (NO3) 3.9H2O and Mn (NO3) 2.4H2O with calcination temperature variation of 900-1100oC. XRD (X-Ray Diffraction) analysis of ceramic Al2O3.MnO2.SiO2 showes peak °2Th=33.2875 intensity relatif=100%, °2Th=55.8688 intensity relatif 24,28%,°2Th=26.1289 intensity relatif 13,22%,°2Th=66.4815 intensity relatif 12,84%,°2Th=35.4375 intensity relatif 11,39%. Ceramic Al2O3.MnO2.SiO2 morphology by SEM (Scanning ElectronMicroscopy) showed that the ceramic at a temperature of 1100oC was homogeneous microscopic. Capacity as measured by the LCR meter instrument empirical equation F (C, T) = 0.01625 T - 11.0833 can be explained that the higher the calcination temperature the higher the value of the capacitor capacity.